Hate in the homeland : the new global far right - Miller-Idriss, Cynthia 1972- (Princeton University Press, 2020)
"Placing space and place at the center of its analysis enables Hate in the Homeland to focus on hate groups and far right extremism not only as static, organized movements but also as flows of youth who move in and out of the periphery and interstitial spaces of far right scenes, rather than only studying youth at the definable or fixed core of far right extremist movements. For many-perhaps even most-far right youth, Miller-Idriss argues that extremist engagement is characterized by a process of moving in and out of far right scenes throughout their adolescence and adulthood in ways that scholars and policymakers have yet to understand. Hate in the Homeland will make a critical intervention into the literature on extremism by showing how youth on the margins are mobilized through flexible engagements in mainstream-style physical and virtual spaces which the far right has actively targeted for this purpose. This approach to far right extremism and radicalization significantly broadens what we know about the far right, and how people engage with it"--